The structure of group preserving operators - Barbieri, Davide (2021)
In this paper, we prove the existence of a particular diagonalization for normal bounded operators defined on subspaces of 2() where is a second countable LCA group. The subspaces where the operators act are invariant under the action of a group Γ which is a semi-direct product of a uniform lattice of with a discrete group of automorphisms. This class includes the crystal groups which are important in applications as models for images. The operators are assumed to be Γ preserving. i.e. they commute with the action of Γ. In particular, we obtain a spectral decomposition for these operators. This generalizes recent results on shift-preserving operators acting on lattice invariant subspaces where is the Euclidean space.